Konsep Konsep Optimalisasi Penggunaan Protein dan Asam Amino pada Ayam Petelur (Ulasan) - Edi, Didik Nur; Setiawanti, St. Theresia Sri Wulandari; Rolin, Maria Karolina Deko (BRILIANT: Jurnal Riset dan Konseptual, 2025)
Essential nutritional components that have an important role in the growth and development of laying hens are protein and amino acids. Protein and amino acids given according to the right levels or dosages in the feed can optimize the health, productivity, and production of laying hens. The advantages and disadvantages of protein and amino acids in feed make feed more expensive, increase ammonia (NH3), and decrease production and productivity of laying hens, especially in the quality of the eggs produced. Therefore, it is necessary to optimize the use of protein and amino acids in feed. The aim is to maximize productivity by making feed formulations according to the needs of laying hens, reducing feed costs, reducing environmental pollution, and increasing profitability. Optimizing the utilization of protein and amino acids can be done with the concept of ideal amino acids, the addition of enzymes, amino acid supplementation, and the idea of reducing crude protein content in feed by emphasizing standard amino acid profile requirements. The principle of optimizing protein use is to balance needs with the amino acid content in feed by paying attention to digestibility.